Towards associative meaningfulness: Maintaining social capital in community development - Ilari Karppi (European Regional Science Association (ERSA), 2012)
The paper consists of three layers that converge on the development of urban communities. Firstly, and empirically it focuses on a particular local development process currently carried out in a rapidly growing urban region in Southern Finland. This process is studied in more detail in the last two sections of the paper with a view on a) what has been accomplished this far and b) what may follow on the basis of past development. The paper's second layer is more conceptual. The scope of this discussion is set with a fair share of ingrained pragmatism, and it will be opened with a deliberatively quick philosophical cut on what may be argued about the potentials and desires of individual citizens in and endeavour to take active roles as co-designers of their living environments. After these introductory lines the focus will be shifted to more or less institutional preconditions that may allow citizens to have such an active role. Found in key positions in this instance is the evolution of institutions that have the capacity to effect in our ways to pursue good and meaningful life. The topic will be discussed within relational spaces set by these institutions – but keeping in mind the actually changing territorial contexts where our everyday experiences unfold. Historically the scope for this unfolding has been made with the help of various systems of belief and knowledge. They still hold a key role in the process of explaining it – and setting narratives for us to grasp how it takes place. The third layer is actually a diagonal that pierces the conceptual and empirical layers. Its core consists of mechanisms that facilitate the impacts that various actors need to use in order to leave their mark in community planning schemes. Not infrequently these mechanisms are something that the actors need to actively find – even if citizen and stakeholder participation is generally a standard feature in planning legislation in all highly developed economies. The planning case discussed in this paper includes a description of measures taken by the studied community planners as they seek to construct the interfaces with which the insights and creativity held by the community members can be embedded in the formal planning process.
Keywords: 330